Efficacy and safety of treatment of HIV-associated multidrug-resistant tuberculosis. Systematic review and meta-analysis - A. V. Kukurika (Журнал инфектологии)
The aim was to conduct a systematic review and meta-analysis of published studies assessing the impact of HIV infection on treatment outcomes and the development of adverse reactions in MDR-TB patients.Material and Methods. We searched for publications using the specified keywords in MEDLINE (PubMed), Google Scholar, and eLibrary databases. Twenty-seven publications with a total number of 13944 patients were selected for meta-analysis. Meta-analysis was performed using Review Manager software (RevMan version 5.4; Cochrane Collaboration, Oxford, UK). Statistical heterogeneity of studies was checked using a Q-test based on χ2. An effect was considered statistically significant at p<0.05.Results. The meta-analysis revealed that the incidence of adverse outcomes in patients 6with MDR-TB/HIV coinfection was higher than in the HIV-free group and was 37%, OR=1.49 [CI: 1.15-1.93]; the incidence of fatal outcomes was 20.3%, OR=2.02 [95% CI: 1.64-2.49]. Among HIV-infected patients, there was a higher incidence of adverse adverse reactions: OSH=1.51 [95% CI: 1.01-2.26], adverse adverse reactions of severe severity: OSH=1.53 [95% DI: 1.1-2.13].Conclusion. The results of the meta-analysis show that patients with MDR-TB/HIV coinfection are characterized by an increased incidence of adverse outcomes and risk of any adverse adverse adverse reactions, further analysis of the problem is needed to optimize treatment outcomes in this population.